2008
DOI: 10.1128/iai.00209-08
|View full text |Cite
|
Sign up to set email alerts
|

Significant Role for ladC in Initiation of Legionella pneumophila Infection

Abstract: Previously, we identified ladC in a cohort of genes that were present in Legionella pneumophila but absent in other Legionella species. Here we constructed a ladC mutant of L. pneumophila and assessed its ability to replicate in mammalian cell lines and Acanthamoeba castellanii. The ladC mutant was recovered in significantly lower numbers than wild-type L. pneumophila at early time points, which was reversed upon transcomplementation with ladC but not ladC N430A/R434A , encoding a putative catalytically inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…A study by Hoffmann et al characterized the bacterial LCV proteome at 1h after infection (29). Hoffmann et al found some of the here described PE-up proteins, including RavZ (124), RalF (119), SidC (111,162), SidM/DrrA (113,115,163) but also some E-up proteins, such as LegS2 (105), LepA (108), and those with equal abundance, such as Lem3 (164), Ceg28/ RidL (165), SdhA (166), SidD (110,167). This shows that a broad variety of Dot/Icm effectors is present in LCV proteomes.…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 99%
“…A study by Hoffmann et al characterized the bacterial LCV proteome at 1h after infection (29). Hoffmann et al found some of the here described PE-up proteins, including RavZ (124), RalF (119), SidC (111,162), SidM/DrrA (113,115,163) but also some E-up proteins, such as LegS2 (105), LepA (108), and those with equal abundance, such as Lem3 (164), Ceg28/ RidL (165), SdhA (166), SidD (110,167). This shows that a broad variety of Dot/Icm effectors is present in LCV proteomes.…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 99%
“…Although it is not very clear how the bacteria are internalized by eukaryotic cells, many reports indicated that different mechanisms of uptake were used by macrophage-like cell and non-phagocytic cell. 5,[19][20][21] Our results indicated that internalization of L. pneumophila by macrophage-like cell lines were easier than that by non-phagocytic cell lines. Correlational analyses from our results showed positive correlation between adherence and invasiveness (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The four sequenced genomes of L. pneumophila contain each an average of 3,000 genes with 200 to 300 genes specific to each genome, but all contain the pmrAB locus. It is important to note that some of the genes present in the clinical strain AA100/130b may be absent in the Philadelphia-1 strain and vice versa and that gene variation among bacterial strains of the same species usually represents a small proportion of the genome (53). Despite potential minor differences between the Philadelphia-1 strain genome and our clinical strain AA100/a30b, ϳ10% of the core genome appears to be under the regulation of PmrA.…”
Section: Discussionmentioning
confidence: 99%